Source Apportionment and Health Risk of Some Organic Contaminants in Water and Suspended Particulate Matter from Imo River, Nigeria - P. J. Nna; K. J. Orie; N. A. S. Kalu (Journal of Applied Sciences and Environmental Management, 2024)
The objective of this study was to provide the source identification and assessment of potential health associated with some organic contaminant detected in water and suspended particle matter (SPM) from the Imo River, Nigeria using gas chromatography with a flame ionization detector (GC/FID) after 1:1 ratio solvent mixture (n-hexane and dichloromethane) extraction. The findings on SPM revealed the values; pH (5.42±0.097-5.567±0.057), conductivity (74.58±5.390-87.6±0.9 uS/cm), and total organic carbon (TOC) (3.626±0.366-6.143±0.176), and surface water; pH (6.077±0.049-6.46±0.52), conductivity (49.03±1.430- 58.12±0.553 uS/cm). The total concentrations of both low and high molecular PAHs in SPM recorded at stations1-3 were 4.384 mg/kg, 16.87 mg/kg, and (22.69 mg/kg); surface water 2.329 mg/L, 7.428 mg/L and 6.657 mg/L. The source apportionment of PAHs in SPM and surface water via molecular diagnostic ratios identified both petrogenic source (crude oil, petroleum spillages, and seepages) and pyrogenic sources (combustion of grass, wood, coal, and gas flaring). A further analysis with Principal Component Analysis (PCA) revealed two principal components, with 65.568% for component 1 and 34.432% for component 2 for SPM, and 62.80% for principal components and 37.2% for principal component 2 for surface water. The correlation analysis of PAHs affirmed common sources such as petrogenic and pyrogenic origins. The toxic equivalent factor of total benzo(a)pyrene for 6 ∑PAHs in SPM was recorded as 3.693 mg/kg, 1.605 mg/kg, and 0.453 mg/kg; surface water was recorded as 0.823 mg/L, 1.858 mg/L, and 0.353 mg/L, while the mutagenic equivalency quantities of SPM were recorded as 3.693mg/kg, 1.146 mg/kg, and 0.316 mg/kg; surface water 0.739 mg/L, 0.938, and 0.577 for stations 1-3. The effect of carcinogenic PAHs in SPM was higher in adults than in children, with regards to ILCR analysis. Users of Imo Rivers should be guided on the exposure of SPM and surface water since the toxic, mutagenic, and cancer risk levels of the river are above the permissible limit in some stations.